Direct Synthesis of Hydrogen Peroxide from Hydrogen and Oxygen Using Tailored Pd Nanocatalysts: A Review of Recent Findings - Seo, Myung-gi; Kim, Ho Joong; Han, Sang Soo; Lee, Kwan-Young (SPRINGER/PLENUM PUBLISHERS, 2017)
Direct synthesis of hydrogen peroxide from hydrogen and oxygen is being actively studied as an alternative to the current manufacturing process. The direct synthesis route has not reached the point of commercialization because of low yields, but significant effort is being spent on enhancing the productivity. With advances in computational capacity, simulation studies based on DFT calculations now offer directions for catalyst improvement, but such modifications can only be realized through the application of nanoparticle synthesis techniques that allow for nanocrystal morphology and size control and unique immobilization. To date, there have only been a small number of studies on such nanoparticles with size and crystallographic homogeneity for the direct hydrogen peroxide synthesis. According to our knowledge no other group has systematically investigated application of nanoparticles in direct synthesis of hydrogen peroxide, and thus included in this review are primarily previous studies conducted by our group. In this review, we discuss the utilization of nanotechnology for the synthesis of Pd catalysts and its effect on the direct synthesis of hydrogen peroxide, and we suggest a direction for future studies.
Keywords: DIRECT H2O2 SYNTHESIS; CATALYTIC-ACTIVITY; PD/SIO2 CATALYST; H-2-TO-H2O2 OXIDATION; SHELL NANOSTRUCTURES; SUPPORTED CATALYSTS; SELECTIVE OXIDATION; PALLADIUM CATALYSTS; REACTION-MECHANISM; SURFACE SITES